Multinational management : a strategic approach - Cullen, John B. 1948- (South-Western College, 1999)
Foundations of multinational management. Strategy content and formulation for multinational companies. Management processes in strategy implementation: design choices for multinational companies. Management processes in strategy implementation: managing people in multinational companies. Ethics and social responsibility in the multinational company.